6 - The Airport Geography of Power as Site and Limit of NEPAD’s Transnational African Assemblage - Masemola, Kgomotso Michael (Africa Development, 2018)
This article mobilises the Deleuzian analytical category of ‘assemblage’ to distinctly bring to view how racial profiling in South African airport spaces operationalises a paradoxical discourse of invidious visibility and invisibility that flies in the face of the New Partnership for African Development (NEPAD) as articulated in the vision embraced by the member states of the African Union, of which South Africa is part. The said discourse, this article argues, runs counter to the spirit of NEPAD as it becomes an inscribing socius in a territorial machine that is geared towards not only processing entries and exits of African migrants into the airport. It recolonises the African airport into a zone of exception, reterritorialising the African assemblage into a space definable by the particularities of race and nation. The airport becomes a veritable zone of exception: no recognition of movement rights for African migrants despite proclamations of priorities of regional integration in Africa. Over South African airports now hover signature meta-narratives that are at variance with NEPAD. Nothing exemplified this more than the unfair detention of Wole Soyinka in a South African airport, especially because the Nobel Laureate was officially invited to give an address in honour of Nelson Mandela.